An Analysis of Social Class and Discrimination in the Movie Saltburn 2023 - Panjaitan, Jodi Ferdianto; Anggraini, Loisti; Beru Sembiring, Lina Tri Astuty; Putra, Dhanu Ario (Universitas Galuh, 2024)
A movie is a series of moving images that contain a story and can be watched by people. In addition to entertaining, movies also have the function of providing knowledge and education. There are various themes that can be made into a movie, one of which is a movie about social class and discrimination. This article analyzes the social class and discrimination that occur in a film entitled Saltburn by Emerald Fennel. This article using Max Weber's theory to classify the social classes found in Saltburn, This article also using Theodorson's theory to analyze discrimination in Saltburn. The method used in writing this thesis is the descriptive-qualitative method. The results of the analysis in this article show the existence of social classes, namely the upper class and the middle class. These social classes show differences in lifestyle and position. In addition, there is also discrimination that occurs in the movie in the form of verbal discrimination. Based on our analysis of the film Saltburn, it can be concluded that the existence of social class can affect the way a person socializes and can also clearly show the social status in the film. In addition, the existence of social class can lead to forms of discrimination, one of which is verbal discrimination. It can also be inferred that the discrimination experienced by Oliver can affect his mindset and the way he lives his life.